2020
DOI: 10.1093/brain/awaa163
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and cellular correlates of human nerve regeneration: ADCYAP1/PACAP enhance nerve outgrowth

Abstract: Abstract We only have a rudimentary understanding of the molecular and cellular determinants of nerve regeneration and neuropathic pain in humans. This cohort study uses the most common entrapment neuropathy (carpal tunnel syndrome) as a human model system to prospectively evaluate the cellular and molecular correlates of neural regeneration and its relationship with clinical recovery. In 60 patients undergoing carpal tunnel surgery [36 female, mean age 62.5 (sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 85 publications
(112 reference statements)
1
82
0
Order By: Relevance
“…Primary publications containing parts of the Oxford CTS cohort have been previously published. 6 , 46 …”
Section: Methodsmentioning
confidence: 99%
“…Primary publications containing parts of the Oxford CTS cohort have been previously published. 6 , 46 …”
Section: Methodsmentioning
confidence: 99%
“…More recently, transcriptional profiling of the skin of patients undergoing surgery for carpal tunnel syndrome revealed that ADCYAP1 (the gene encoding for PACAP) was the most robustly up-regulated and its expression was associated with nerve recovery. Additionally, when human induced pluripotent stem cell-derived sensory neurons were treated with PACAP, it enhanced axonal outgrowth in a dose dependent manner [36]. Together, these studies suggest a prominent role of PACAP induced PAC1 activity in mediating neuronal survival, axon regeneration and remyelination following peripheral nerve injury.…”
Section: Discussionmentioning
confidence: 72%
“…More recently, transcriptional profiling of the skin of patients undergoing surgery for carpal tunnel syndrome revealed that ADCYAP1 (the gene encoding for PACAP) was the most robustly upregulated and its expression was associated with nerve recovery. Additionally, when human induced pluripotent stem cell-derived sensory neurons were treated with PACAP, the peptide enhanced axonal outgrowth in a dose dependent manner [36]. Together, these studies suggest a prominent role of the PACAP/PAC1 axis in mediating neuronal survival, axon regeneration and remyelination following peripheral nerve injury.…”
Section: Discussionmentioning
confidence: 74%